2017
DOI: 10.1177/1010428317691682
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs regulate the epithelial–mesenchymal transition and influence breast cancer invasion and metastasis

Abstract: MicroRNAs are small RNA molecules that play a major role in the post-transcriptional regulation of genes and influence the development, differentiation, proliferation, and apoptosis of cells and the development and progression of tumors. The epithelial-mesenchymal transition is a process by which epithelial cells morphologically transform into cells with a mesenchymal phenotype. The epithelial-mesenchymal transition plays a highly important role in tumor invasion and metastasis. Increasing evidence indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 85 publications
(123 reference statements)
1
28
0
1
Order By: Relevance
“…Recent studies have found that ZEB1 is rarely expressed in epithelial tissues and highly differentiated tumor tissues, but it is highly expressed in poorly differentiated tumors, especially in the invasive part. 23,24 In our study, we found that up-regulated GRHL2 directly inhibited the expression of ZEB1, indirectly inhibited the expression of E-cadherin and up-regulated the expressions of Vimentin, Snail and Slug, and vice versa. This indicated that GRHL2 was crucial in regulation of EMT.…”
Section: Discussionsupporting
confidence: 49%
“…Recent studies have found that ZEB1 is rarely expressed in epithelial tissues and highly differentiated tumor tissues, but it is highly expressed in poorly differentiated tumors, especially in the invasive part. 23,24 In our study, we found that up-regulated GRHL2 directly inhibited the expression of ZEB1, indirectly inhibited the expression of E-cadherin and up-regulated the expressions of Vimentin, Snail and Slug, and vice versa. This indicated that GRHL2 was crucial in regulation of EMT.…”
Section: Discussionsupporting
confidence: 49%
“…miRNAs are considered as a group of small non-coding RNA molecules that exhibit different roles in some biological behaviors, for instance, cell apoptosis, differentiation, and tumorigenesis (19). Recently some studies have reported the role of miRNAs in modulating invasion and metastasis of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that EMT is important for the metastasis of breast cancer [13,14]. EMT-related microRNAs can regulate EMT, invasion, and metastasis in breast cancer [15]. Twist, a key transcription factor for EMT, also promotes tumor metastasis in basal-like breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%